SUBSTITUSI DALAM CERITA PENDEK â€œTHE GARDEN PARTYâ€ KARYA KATHERINE MANSFIELD: SUATU ANALISIS SINTAKSIS - Nday, Grace Resthyani (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This skripsi entitled Substitution in the short story â€œThe Garden Partyâ€ by Katherine Mansfield: Syntactical Analysis. One of the ways to avoid redundant repetition in English is by using the pattern of substitution. It can also help the reader to understand the text correctly. The aims of this research are to identify, classify, and describe the kinds of substitute or pro-form in the short story â€œThe Garden Partyâ€. In classifying and analyzing the data, the writer uses Aarts and Aartsâ€™ theory (1982). This research uses descriptive method. The results of this research show that there are four kinds of substitution in short story â€œThe Garden Partyâ€ by Katherine Mansfield namely pro-forms to replace a noun phrase, pro-forms to replace a verb phrase, pro-forms to replace a clause and pro-forms to replace adverbial of time and place.